2015
DOI: 10.1086/680022
|View full text |Cite
|
Sign up to set email alerts
|

Variable Environmental Effects on a Multicomponent Sexually Selected Trait

Abstract: Multicomponent signals are made up of interacting elements that generate a functional signaling unit. The interactions between signal components and their effects on individual fitness are not well understood, and the effect of environment is even less so. It is usually assumed that color patterns appear the same in all light environments and that the effects of each color are additive. Using guppies, Poecilia reticulata, we investigated the effect of water color on the interactions between components of sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 82 publications
3
67
0
Order By: Relevance
“…We found that males with larger violet patches spent more time in the F55 (lilac) environment and males with larger silver patches spent more time in the clear environment. This is an exciting result that supports other studies that have shown that females prefer combinations of male colour patches that include colours that 'match', and therefore, reflect most intensively, the light environment [7]; the more light a colour patch can reflect, the more conspicuous the patch should be. For example, a violet spot in light containing little short or medium wavelength light (such as F55 and clear) will appear dark because it does not reflect much of the available light.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…We found that males with larger violet patches spent more time in the F55 (lilac) environment and males with larger silver patches spent more time in the clear environment. This is an exciting result that supports other studies that have shown that females prefer combinations of male colour patches that include colours that 'match', and therefore, reflect most intensively, the light environment [7]; the more light a colour patch can reflect, the more conspicuous the patch should be. For example, a violet spot in light containing little short or medium wavelength light (such as F55 and clear) will appear dark because it does not reflect much of the available light.…”
Section: Discussionsupporting
confidence: 84%
“…Our results suggest that males with more highly contrasting colour patterns that are more attractive [7], court more frequently. This relationship is also stronger in the presence of more receptive females which implies that this is a reaction to positive feedback from females, as has been suggested by previous studies [44,45].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations